Editor's Comments - Kilduff, Martín (Academy of Management Review, 2006)
This article discusses changes within the staff of the journal, “Academy of Management Review.” New associate editor, Linda Treviño, is introduced. Treviño is a professor of organizational behavior and has pioneered research on the management of ethical conduct within organizations. It is mentioned that she received the Academy of Management Review award for best article in 1992 for her article on the social effects of punishment. The author thanks former associate editor, Professor Thomas Donaldson, for his contributions as he retires. Donaldson helped to establish the journal as a leader in research on topics such as business ethics and corporate governance.